Atmospheric and soil moisture controls on evapotranspiration from above and within a Western Boreal Plain aspen forest. Issue 15 (26th July 2013) - Brown, S. M.; Petrone, R. M.; Chasmer, L.; Mendoza, C.; Lazerjan, M. S.; Landhäusser, S. M.; Silins, U.; Leach, J.; Devito, K. J.
Abstract The Western Boreal Plain of North Central Alberta comprises a mosaic of wetlands and aspen (Populus tremuloides) dominated uplands where precipitation (P) is normally exceeded by evapotranspiration (ET). As such these systems are highly susceptible to the climatic variability that may upset the balance between P and ET. Above canopy evapotranspiration (ETC) and understory evapotranspiration (ETB) were examined using the eddy covariance technique situated at 25.5 m (7.5 m above tree crown) and 4.0 m above the ground surface, respectively. During the peak period of the growing seasons (green periods), ETC averaged 3.08 mm d−1 and 3.45 mm d−1 in 2005 and 2006, respectively, while ETB averaged 1.56 mm d−1 and 1.95 mm d−1. Early in the growing season, ETB was equal to or greater than ETC once understory development had occurred. However, upon tree crown growth, ETB was lessened due to a reduction in available energy. ETB ranged from 42 to 56% of ETC over the remainder of the snow‐free seasons. Vapour pressure deficit (VPD) and soil moisture (θ) displayed strong controls on both ETC and ETB. ETC responded to precipitation events as the developed tree crown intercepted and held available water which contributed to peak ETC following precipitation events >10 mm. While both ETC and ETB were shown to respond to VPD, soil moisture in the rooting zone is shown to be the strongest control regardless of atmospheric demand. Further, soil moisture and tension data suggest that rooting zone soil moisture is controlled by the redistribution of soil water by the aspen root system. Copyright © 2013 John Wiley & Sons, Ltd.